Role of Decision Making Process of Farm Women Regarding Vegetable Operation - D.K. Singh , Pramod Singh Thakur, Deepmala Singh and Anjani Kumar, (Indian Journal of Extension Education, 2015)
Decision making is the process of consciously choosing courses of action from available alternatives and integration ofthem for the purpose of achieving the desired goal. Farm women are participated in most of the important agriculturaloperations like field preparation, sowing of seed, planting of seedlings inter-cultivation, weeding and plant protectionmeasures, picking & harvesting, compost making application of manures and fertilizers, cleaning of farm products. Invegetable cultivation, decision making always remained associated with the farm women utilization relating to variousaspects in the study area, yet their involvement in this process has not been recognized. It was evident from vegetablecultivation, the joint decisions by male and female partners of the household are important. The present study wasconducted in Panagar block of Jabalpur district. A list of vegetables growing villages was prepared with the help ofextension official out of these only 5 villages were selected randomly due to major vegetable growing area. Arepresentative sample of 110 vegetable growers was drawn from the selected villages. During the research study, it wasobserved that majority of farm women had always taken decision regarding selection of crop, quantity of seed, sowingtime of seed, weeding, use of manures, harvesting, picking and seed storage. They were rarely involved in decisionmaking regarding nursery management, field preparation, selection of variety, irrigation, seed treatment and marketingand use of fertilizers, plant protection measures as it required more scientific knowledge and skill.